Detecting DDOS Attacks Amidst Flash Crowds Using Machine Learning - Abdulkadir, Maryam; Aminu Ahmad, Muhammad; Abubakar Aliyu, Ahmad; Abdulkadir, Sa’adatu; Ibrahim, Mohammed; Abdullahi, Adamu; Muazu Ahmed, Abubakar (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
In the digital landscape, distinguishing genuine flash crowds from Distributed Denial of Service (DDoS) attacks remains a critical challenge. Flash crowds, characterized by sudden surges of legitimate traffic, often exhibit behavioral patterns similar to DDoS attacks, leading to false positives in detection systems. This research proposes a robust machine learning-based approach for setting apart flash crowds from DDoS attacks, using a multi-classification methodology. The implemented system leverages a Random Forest classifier trained on network traffic data, focusing on key features such as packet size, flow duration, and transmission rates. The dataset is pre-processed to handle anomalies and class imbalance using the Synthetic Minority Over-sampling Technique (SMOTE). Evaluation metrics such as accuracy, precision, recall, and F1-score, demonstrated the system's effectiveness, achieving over 99% accuracy in distinguishing benign traffic from malicious attacks. Additionally, advanced visualizations such as confusion matrices and ROC curves provided actionable insights into the model performance. The new model's scalability and high accuracy make it a promising solution for real-time applications in network anomaly detection, ensuring minimal disruption to legitimate user activities. This study contributes to the ongoing efforts to enhance cyber-security defenses against evolving DDoS threats while preserving the accessibility of web services during legitimate traffic surges.